Attaining Sustainable Development Goals (SDGs): New evidence on foreign aid and the "bundling" of domestic revenue mobilization in sub-Saharan Africa - Oludele Folarin; Isiaka Akande Raifu (African Governance and Development Institute (AGDI), 2022)
With the global sustainable development goals, it has become imperative for developing countries, especially sub-Saharan African countries, to think inward on ways to increase domestically mobilized revenue. The recovery of the global economy within the last few years has increased foreign assistance inflow into African countries. However, the direction of its impact on domestic mobilized revenue is unclear. This study revisited the relationship between foreign aid and domestic mobilized revenues for 32 sub-Saharan African countries using a more recent and novel dataset on tax revenue. We employed instrumental fixed effect Quantile regression, a novel technique in aid and tax revenue literature. The study findings show that the impact of foreign aid varies across tax revenue distribution. We found a negative and significant effect in countries with high tax effort, while the effect is insignificant in countries with low tax effort sub-Saharan African countries, especially those with low tax revenue, need to use foreign aid to strengthen their tax administration and adopt modern tax revenue collection technologies. As a result, sub-Saharan African countries should request advanced countries or donors to provide technical support in tax revenue mobilization.
Keywords: F35; H2; H27; 330; Foreign aid; Tax revenue; Quantile regression; Sub-Saharan Africa